Lingkungan Kerja dan Kepuasan Kerja Dosen - Ardin Ardin (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
The object of this research is to obtain information about the effect of work environment on job satisfaction. It was quantitative research with survey method inThe State Islamic Institute Kendari southeast Sulawesi.The research was conducted to all lecturer of The State Islamic Institute Kendari Southeast Sulawesi by using a survey method with path analysis applied in testing hypothesis.There is76 employees are used as a sample was selected by using Slovin formula. The research conlude: There is a direct positive effect of work environment onjob satisfaction The State Islamic Institute of Islam (IAIN) Kendari Southeast Sulawesi. Keywords: Work Environment and Job Satisfaction